1998
DOI: 10.1099/0022-1317-79-12-3067
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in vitro and in vivo by H-1 parvovirus infection.

Abstract: Apoptosis induced by H-1 parvovirus infection was investigated in C6 rat glioblastoma cells and in newborn rats. Apoptotic changes, such as chromatin condensation, the appearance of apoptotic nuclear bodies and oligonucleosomal DNA ladders, were observed in infected C6 cells 2 days after infection. Inhibitor assay results suggest that a caspase-3-dependent apoptosis activation pathway is induced by H-1 virus infection in C6 cells. Observations made in vivo revealed that the number of apoptotic cells increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
38
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 23 publications
3
38
0
Order By: Relevance
“…H1 virus was also able to induce programmed cell death in human hepatoma cells, as it was shown for other cell types and by other hepatotropic viruses. 18,19,35,37 In several cases, tumor cells were more sensitive to H1 -induced toxicity than their nontransformed parental cells. 12,22,23 Thus, human hepatoma cells constitute an additional system in which a selective killing by H1 virus could be achieved in the transformed, but not in the primary, hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…H1 virus was also able to induce programmed cell death in human hepatoma cells, as it was shown for other cell types and by other hepatotropic viruses. 18,19,35,37 In several cases, tumor cells were more sensitive to H1 -induced toxicity than their nontransformed parental cells. 12,22,23 Thus, human hepatoma cells constitute an additional system in which a selective killing by H1 virus could be achieved in the transformed, but not in the primary, hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…This study focuses on rat H-1PV, which infects and kills human tumor cell lines of various origins (e.g., of brain [23], pancreas [4,14], blood [3], colon [38], cervix [20], and breast [66,67]) and which is currently under evaluation in a phase I/IIa clinical trial for the treatment of patients with recurrent glioblastoma multiforme (57). H-1PV has the ability to induce different cell death pathways in cancer cells, including necrosis (53), apoptosis (28,46,54,65), and lysosome-dependent cell death (16), while sparing nontransformed cells. Recently, we have reported the capacity of the virus to induce oxidative stress in cancer cells leading to DNA damage, cell cycle arrest, and apoptosis.…”
mentioning
confidence: 99%
“…Certain autonomous parvoviruses were assumed to induce apoptosis in infected cells (4,11,12,15,18,26). Our previous study (15) demonstrated caspase-3-dependent apoptosis in H-1 virus-infected C6 cells.…”
mentioning
confidence: 99%